STRATEGIES FOR CULTURAL ADAPTATION IN VOCATIONAL EDUCATION INSTITUTIONS UNDER GLOBALIZATION - Abdulmajeed Nabeel Azouz, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The study examines the role of cultural adaptation strategies in enhancing the effectiveness of vocational education institutions under conditions of globalization. It analyzes how cultural factors such as societal values, traditions, and institutional norms influence the implementation of global educational models. The research highlights the importance of aligning international standards with local contexts to ensure sustainable reforms, improved learning outcomes, and stronger labor market integration.